Differential associations between state-level educational quality and cardiovascular health by race: Early-life exposures and late-life health - Anusha M. Vable; Thu T. Nguyen; David Rehkopf; M. Maria Glymour; Rita Hamad (Elsevier, 2019)
Cardiovascular diseases (CVD) are patterned by educational attainment but educational quality is rarely examined. Educational quality differences may help explain racial disparities. Health and Retirement Study respondent data (1992-2014; born 1900-1951) were linked to state- and year-specific educational quality measures when the respondent was 6 years old. State-level educational quality was a composite of state-level school term length, student-to-teacher ratio, and per-pupil expenditure. CVD-related outcomes were self-reported (N = 24,339) obesity, heart disease, stroke, ever-smoking, high blood pressure, diabetes and objectively measured (N = 10,704) uncontrolled blood pressure, uncontrolled blood sugar, total cholesterol, high-density lipoprotein cholesterol (HDL), and C-reactive protein. Race/ethnicity was classified as White, Black, or Latino. Cox models fit for dichotomous time-to-event outcomes and generalized estimating equations for continuous outcomes were adjusted for individual and state-level confounders. Heterogeneities by race were evaluated using state-level educational quality by race interaction terms; race-pooled, race by educational quality interaction, and race-specific estimates were calculated. In race-pooled analyses, higher state-level educational quality was protective for obesity (HR = 0.92; 95%CI(0.87,0.98)). In race-specific estimates for White Americans, state-level educational quality was protective for high blood pressure (HR = 0.95; 95%CI(0.91,0.99). Differential relationships among Black compared to White Americans were observed for obesity, heart disease, stroke, smoking, high blood pressure, and HDL cholesterol. In race-specific estimates for Black Americans, higher state-level educational quality was protective for obesity (HR = 0.88; 95%CI(0.84,0.93)), but predictive of heart disease (HR = 1.07; 95%CI(1.01,1.12)), stroke (HR = 1.20; 95%CI(1.08,1.32)), and smoking (HR = 1.05; 95%CI(1.02,1.08)). Race-specific hazard ratios for Latino and Black Americans were similar for obesity, stroke, and smoking. Better state-level educational quality had differential associations with CVD by race. Among minorities, better state-level educational quality was predominately associated with poorer CVD outcomes. Results evaluate the 1900-1951 birth cohorts; secular changes in the racial integration of schools since the 1950s, means results may not generalize to younger cohorts. Keywords: Education, Race, Heart disease, Stroke, Hypertension, Health disparities, Obesity, Smoking